Painting a Picture of Alberta History - Tupper, Jennifer (Journal of the Canadian Association for Curriculum Studies, 2025)
Painted by Henry G. Glyde in 1951, the Alberta History mural has been a fixture in the University of Alberta’s Rutherford South Library Reading room for more than 70 years. In the last decade, it has come under scrutiny for its problematic representation of the province’s past, sparking public dialogue and a process of consultation to determine its future. This paper examines how the mural, as public art, contributes to a lived curriculum of settler colonialism at a time when the Truth and Reconciliation Commission of Canada (2015) asks that institutions “support, promote, and facilitate truth . . . [and demonstrate] a profound commitment to establishing new relationships embedded in mutual recognition and respect that will forge a brighter future” (p. 339). Drawing on understandings of public pedagogy, theories of settler geographical ignorance, ethical relationality and difficult knowledge, this paper questions the production of a settler colonial consciousness and its role in normalizing the settler experience while marginalizing, misrepresenting or making invisible the perspectives and experiences of Indigenous Peoples. By challenging dominant narratives of Canadian history that are part of the lived curriculum of place and public art, and by re-imagining them through the lens of ethical relationality, this paper aims to confront and disrupt colonial harm and settler colonial consciousness.